The Spirits of Neoliberal Reforms and Everyday Politics of the State in Africa - (:unkn) unknown (My University, 2016)
This book, composed of articles first published in the journal Politique africaine, proposes an original interpretation of neoliberalism in Africa. Instead of seeing neoliberal reforms as intrinsically destructive of the post-colonial state, the authors, who include some of Africa’s best-known social scientists, focus on the resilience and adaptability of African state structures, economic systems, and social survival mechanisms and examine the diversity of responses to neoliberalism in what the editors call the “everyday politics of the state.” In essays that range from diverse theoretical or historical discussions to close studies of the dynamics of specific reforms in particular places, they argue against univocal interpretations of the effects of neoliberalism. They show that the African state, far from disappearing, is adapting and reconfiguring itself in fascinating new social realities “co-constructed” by state action as well as by the improvisations of communities and other private actors. (Publisher's abstract)
Keywords: African Research